Exploring the consequences of erratic data reporting for cross-national research on homicide - Messner, Steven F. (Journal of quantitative criminology, 1992)
This paper examines the common practice in cross-national research on homicide of using crime estimates for a multiyear period based on a smaller number of years than theoretically desired because of erratic data reporting for selected nations. Correlations between hypothetical baseline rates and various alternative estimates are examined to simulate the potential consequences of using temporally incomplete data rather than data for the full multiyear period of interest. The results reveal that this common practice is likely to be highly acceptable for certain national samples but less acceptable for others. The paper concludes with suggestions for dealing with potentially problematic cases.